Synthesis and antibacterial activity of monocyclic 3-carboxamide tetramic acids - Jeong, Yong-Chul; Moloney, Mark G. (Beilstein Journal of Organic Chemistry, 2013)
A chemical library of carboxamide-substituted tetramates designed by analogy with antibacterial natural products, a method for their rapid construction, and the evaluation of their antibacterial activity is reported.
Keywords: acylation; antibacterial; drug discovery; natural products; tetramate